Multiple Episodes of Remote Brightenings Driven by a Coronal Extreme-ultraviolet Jet on the Sun - Chao Zhang; Zhenghua Huang; Hengyuan Wei; Youqian Qi; Mijie Shi; Hui Fu; Xiuhui Zuo; Weixin Liu; Mingzhe Sun; Ming Xiong; Lidong Xia (The Astrophysical Journal)
Remote brightening (RB) is compact brightening at footpoints of magnetic loops, which are remotely connecting to and confining an eruption in the solar atmosphere. Here, we report on observations of an RB resulting from an EUV jet with a speed of about 90 km s ^−1 . The loops connecting the RB and the jet have an apparent length of about 59 Mm. Intriguingly, the RB exhibits at least two episodes of brightenings, as characterized by two peaks in its lightcurve. The energies that sustain the first and second peaks of the RB are 6.3 × 10 ^26 erg and 8.4 × 10 ^26 erg, respectively, and comprise a significant proportion of the total energy. The first peak of the RB brightenings coincides with the jet's peak with a time delay of 12 s, while the second peak lags behind by 108 s. Besides the flows of the ejecta, we have identified two additional flows originating from the eruption site. One is relatively cool with a temperature of ${{\rm{log}}}_{10}(T/{\rm{K}})=5.8$ –6.1 and a speed of about 275 ± 15 km s ^−1 . The other is hot with a temperature of ${{\rm{log}}}_{10}(T/{\rm{K}})=7.0$ –7.3 and a much greater speed of about 750 ± 70 km s ^−1 . We attribute the second peak of RB directly to this hot flow, which our numerical experiments suggest is the result of a slow shock wave. Considering the minimal time delay between the first peak of RB and the eruption, we infer that this first episode is due to heating by nonthermal electrons. Our research demonstrates that the dynamics in an RB can offer vital insights into the nature of the corresponding eruption and help understand how energy is distributed throughout the solar atmosphere.